Infrastructure policy and training environment in shaping pencak silat athlete achievement: A qualitative case study in Central Java - Ihda Diyaur Rahman; Agus Kristiyanto; Rony Syaifullah (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
This study examines how infrastructure policy, facility access, and training system implementation shape pencak silat athlete achievement in Central Java, Indonesia. In many provincial contexts, formal sport policies are not always accompanied by sport-specific infrastructure and stable access, creating gaps between policy design and training practice. A qualitative case study was conducted using criterion-based purposive sampling involving six stakeholders representing policy, administration, coaching, and athlete perspectives within the provincial sport system. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and analyzed using reflexive thematic analysis emphasizing iterative coding and interpretive engagement across data sources. Interviews were guided by a protocol developed from the research questions, observations focused on training practices and facility use, and documents provided contextual policy evidence. The findings suggest that although pencak silat is formally recognized within provincial sport governance, infrastructure support remains general and not yet translated into sport-specific provision, facility access is uneven across training contexts, and training continuity is maintained through adaptive coaching practices and institutional coordination, resulting in athlete achievement that appears stable but reflects an effective yet fragile support system that depends more on human and organizational capacity than on stable structural support. This study contributes to the sport development literature by demonstrating that athlete achievement is an environmentally conditioned outcome shaped by the interaction between policy conditions, access arrangements, and adaptive training practices within a provincial sport environment. The findings indicate the need for more sport-specific infrastructure planning, stable facility access, and stronger coordination among sport institutions.